Accounting Information System Quality's Effect on Accounting Information Quality - Rapina Rapina; Yenni Carolina; Joni Joni; Ridwan Ridwan (Research Synergy Foundation, 2023)
This study aims to examine the extent to which accounting information system quality influences accounting information quality. This study's demographic consisted of accounting and finance personnel in Indonesia. The purposive sampling strategy was used in this investigation, and the method used is a survey method. Primary data are used, which are processed statistically using SEM Partial Least Square (PLS) questionnaires as the research instrument. The statistical analysis method uses SEM because there may be a causal relationship between the variables, and each variable is not observed. According to the study's findings, the effectiveness of accountability information systems influences the effectiveness of accountability information. According to the concept, the successful application of accounting information systems helps users make decisions. Additionally, performance will be impacted by the caliber of accounting data.